Supporting Service Composition with Ontology-based UPnP AV Architecture in AV Environment - Kelvin Choy Chuong, Wen; Tan Su, Wei; Wong Sau, Peng; Mohamad Zaini, Norliza (2008)
The current trend in digital home technologies is slowly moving towards creating entertainment experience where users can enjoy any multimedia contents conveniently with minimal manual configuration. Automated service composition is useful in enhancing the entertainment experience through coordination among existing services to fulfill user request. UPnP AV architecture is well adopted for building consumer-oriented AV products with simple installation and configuration setting. However, not all services specified in UPnP AV architecture is useful for automating service composition. Thus, in this paper, we propose a methodology to organize the information advertised by UPnP AV devices and selectively add the information into ontology to support service composition. We focus our research on AV home network environment. With the ontology, complex service composition can be performed easily so that a better entertainment experience can be offered to the users.